No midterm advantages in the middle term using small intestinal submucosa and human amniotic membrane in Achilles tendon transverse tenotomy. Issue 1 (December 2016) - Liu, Yushu; Peng, Yinbo; Fang, Yong; Yao, Min; Redmond, Robert; Ni, Tao
Abstract Background The study was aimed to compare the effects of small intestinal submucosa (SIS) and human amniotic membrane (HAM) on Achilles tendon healing. Methods A total of 48 New Zealand white rabbits were divided into two groups. A full-thickness transverse tenotomy was made at the right leg of the rabbits. Then, the laceration site was wrapped with HAM (P/A group) or SIS (P/S group). The ultimate stress (US) and Young's modulus (E ) of the tendons were detected for biomechanical analysis. Histological evaluation was performed using hematoxylin and eosin, immunohistochemical, and immunofluorescent stain. Expression of collagen I was detected by western blot analysis, and levels of inflammatory cytokines IL-1β, IL-6, and TNF-α were measured. Finally, adhesion formation was evaluated. Results There were no significant differences in filamentous adhesion, cross-sectional areas of the laceration sites, levels of inflammatory response, and collagen type I expression between the P/A and P/S groups (p > 0.05). Compared with the P/A group, the US andE values were significantly higher in the P/S group at day 7 (p < 0.05) and at day 14 (p < 0.05). In addition, vascularity was significantly higher in the P/S group than that in the P/A group at day 3 (p < 0.05), day 7 (p < 0.01), and day 9 (p < 0.05). Conclusions SIS showed superior biomechanical properties and neovascularization over HAM in treatment of Achilles tendon injury in the early stage of healing.